"\\displaystyle\n\n(D^2 - 3D + 2)y = \\frac{1}{1 + e^{-x}}\\\\\n\n\n\\textsf{The auxiliary equation is}\\\\\n\nm^2 - 3m + 2 = 0\\\\\n(m - 1)(m - 2) = 0\\\\\nm = 1, 2\\\\\n\n\ny = y_p + y_c\\\\\n\n\ny_c \\, \\textsf{is the complementary factor}\\\\\n\ny_p \\, \\textsf{is the particular Integral}\\\\\n\ny_c = Ae^x + Be^{2x}\\\\\n\ny_p = V_1(x)e^{2x} + V_2(x)e^{x}\\\\\n\n\nW(x) \\, \\textsf{is the Wronskian of the solution}\\\\\n\nW(x) = e^{\\int 3 \\, \\mathrm{d}x}= e^{3x}\\\\\n\n\\begin{aligned}\nV_1(x) &= -\\int \\frac{e^x}{e^{3x}(1 + e^{-x})}\\, \\mathrm{d}x\\\\\n& = -\\int \\frac{e^{-2x}}{1 + e^{-x}}\\, \\mathrm{d}x\\\\\n&= -\\int \\frac{e^{-x}\\cdot e^{-x}}{1 + e^{-x}}\\, \\mathrm{d}x\\\\\n&= \\int \\frac{e^{-x}}{1 + e^{-x}}\\, \\mathrm{d}(e^{-x})\\\\\n&= \\int \\left(1 - \\frac{1}{1 + e^{-x}}\\right) \\mathrm{d}(e^{-x})\\\\\n&= e^{-x} - \\ln(1 + e^{-x}) + C\n\\end{aligned}\\\\\n\n\\begin{aligned}\nV_2(x) &= \\int \\frac{e^{2x}}{e^{3x}(1 + e^{-x})}\\, \\mathrm{d}x\\\\\n& = \\int \\frac{e^{-x}}{1 + e^{-x}}\\, \\mathrm{d}x\\\\\n&= -\\int \\frac{1}{1 + e^{-x}}\\, \\mathrm{d}(e^{-x})\\\\\n&= -\\ln(1 + e^{-x}) + C\n\\end{aligned}\\\\\n\n\\textsf{The constants can be ignored, since we are}\\\\\\textsf{trying to discover non-constant solution to the DE}\\\\\n\n\\begin{aligned}\ny &= Ae^{x} + Be^{2x} -e^{x}\\ln(1 + e^{-x}) \\\\&+ e^{2x}(e^{-x} - \\ln(1 + e^{-x}))\n\\end{aligned}\\\\\n\n\ny = Ae^{x} + Be^{2x} -e^{x}\\ln(1 + e^{-x}) + e^{x} - e^{2x}\\ln(1 + e^{-x})\\\\\n\n\n\\therefore y = Ae^{x} + Be^{2x} - (e^{x}+e^{2x})\\ln(1 + e^{-x}) + e^x"
Comments
Leave a comment